Comprehensive Care Models: Integrating Radiological Technology, Nursing, Laboratory Technicians, and Public Health - Ahmed Mutlaq Alotaibi, Adel Ahmad Saeed Al Ghamdi, Eid Homood Nasser Alhabi, Eizadeen Abdu Mohammed Hamdi, Jibreel Mohammad Ibrahim Ogdy,,; Samia Mosleh Alanazi, Ashwaq Atta Ajaj Alkuwaykibi, Adel Abdullah Saeed Alshahrani, Tahani Lafi Aldhafeeri, Mohammed Saleh Saud Alshammari, Saeed Mohammed Alshehri, Abdulmohsen Hamad Abdulwahab, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The integration of diverse healthcare professions into a comprehensive care model is essential to enhancing patient outcomes and ensuring efficient, patient-centered care. This paper explores the role of radiological technology, nursing, laboratory technicians, and public health in a coordinated healthcare framework. By leveraging the expertise of each discipline, healthcare providers can work collaboratively to improve diagnosis, treatment, prevention, and health promotion. The paper outlines the responsibilities of each profession, the benefits of an integrated approach, and the challenges that may arise in creating such models. Furthermore, it discusses strategies for overcoming barriers to integration and enhancing the efficacy of this model. The ultimate goal is to highlight how integrated care models contribute to holistic patient management, improved health outcomes, and more efficient healthcare delivery.